Antioxidant activity and phytochemical screening of capitula of Tagetes filifolia Lag. or “pacha anís” - Sánchez-Humala, R. (2017)
Objective: To study the antioxidant activity and phytochemical screening of capitula of Tagetes filifolia Lag. “pacha anís”. Materials and methods: An experimental study which used 5 kg of capitula of a medicinal plant called Tagetes filifolia Lag. collected from the Department of Junín, Peru. The phytochemical screening method proposed by Olga Lock, M.D. was used for the phytochemical screening and the DPPH method for the determination of the antioxidant activity. The sample was divided into 3 groups: ether, ethyl alcohol and distilled water at concentrations of 100, 50 and 5 μg/ml, respectively. Results: Abundant amounts of phenols were found in both the distilled water extract and the ethyl alcohol extract, and the latter had moderate amounts of quinones. Besides, the ethyl alcohol extract showed the largest percentage of freeradical scavenging (91.26%) at a concentration of 100 μg/ml. Similar results were found in the ether extract (88.94%) and the distilled water extract (75.58%). Conclusions: The main chemical components were phenols and quinones. The highest antioxidant effect was obtained from the ethanolic extract of Tagetes filifolia Lag. at a concentration of 100 μg/ml.